2020
DOI: 10.3390/molecules25143170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fatty Acid Composition Underlying Hypothalamic Inflammation in Aged Mice

Abstract: Degenerative diseases, which can develop during aging, are underlined by inflammatory processes. Hypothalamic inflammation triggered by elevation in circulating fatty acid levels is directly coupled to metabolic disorders. The present study aimed to investigate and characterize the hypothalamic inflammation and composition of fatty acids in the hypothalami of aged mice. We verified that inflammation and microglial activation occur in the hypothalami of aged mice by performing quantitative real-time PCR and usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…By Western blot analysis with an antibody that recognizes human and mouse APP, 2- to 3-fold higher APP levels were observed in hAPP WT as compared with WT mice at early (3–4 months old: 2.67 ± 0.34), advanced (6–8 months old: 1.86 ± 0.21), and late ages (11–12 months old: 2.63 ± 0.30) ( Figure 2, A and B ) as expected ( 32 ). A trend of a higher expression of brain Ppara was observed together with a trend of increased Acox1 , Cpt1a , and Pdk4 mRNA levels along with age in WT mice ( Figure 2, C–F ), indicating that the aged brain retains enhanced FA utilization compared with young WT mice, meaning that aging brain could switch to FA oxidation ( 33 , 34 ). While a similar profile was observed in hAPP WT mice at early and advanced ages, a 2- to 5-fold decrease in Ppara , Acox1 , Cpt1a , and Pdk4 mRNA levels was observed (0.46 ± 0.04, 0.58 ± 0.06, 0.50 ± 0.10, 0.91 ± 0.06, respectively) in 11- to 12-month-old hAPP WT mice compared with WT littermates at the same age ( Figure 2, C–F ), an age at which severe cognitive deficits are detected ( 32 , 35 ).…”
Section: Resultsmentioning
confidence: 95%
“…By Western blot analysis with an antibody that recognizes human and mouse APP, 2- to 3-fold higher APP levels were observed in hAPP WT as compared with WT mice at early (3–4 months old: 2.67 ± 0.34), advanced (6–8 months old: 1.86 ± 0.21), and late ages (11–12 months old: 2.63 ± 0.30) ( Figure 2, A and B ) as expected ( 32 ). A trend of a higher expression of brain Ppara was observed together with a trend of increased Acox1 , Cpt1a , and Pdk4 mRNA levels along with age in WT mice ( Figure 2, C–F ), indicating that the aged brain retains enhanced FA utilization compared with young WT mice, meaning that aging brain could switch to FA oxidation ( 33 , 34 ). While a similar profile was observed in hAPP WT mice at early and advanced ages, a 2- to 5-fold decrease in Ppara , Acox1 , Cpt1a , and Pdk4 mRNA levels was observed (0.46 ± 0.04, 0.58 ± 0.06, 0.50 ± 0.10, 0.91 ± 0.06, respectively) in 11- to 12-month-old hAPP WT mice compared with WT littermates at the same age ( Figure 2, C–F ), an age at which severe cognitive deficits are detected ( 32 , 35 ).…”
Section: Resultsmentioning
confidence: 95%
“…Further, it was recently demonstrated that microglia, bone-marrow derived macrophages, may maintain their pool without significant substitution by circulating monocytes after their establishment in early postnatal life, even under conditions of chronic HFD feeding [ 70 ]. Here, for immunofluorescence labeling of microglial cells in hypothalamic sections, we used Iba1, which is a molecular marker for active microglia participating in membrane ruffling and phagocytosis [ 59 ]. Iba1 is also known to increase the expression of inflammatory chemokines and cytokines [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total staining intensity was expressed by integrated density (mean gray value x area) using the ROI manager and the background subtraction function of ImageJ. The reactive state of microglial cells is frequently measured by fluorescence intensity of Iba1 or by percentage of Iba1-stained area [ 37 , 45 , 56 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…The extraction and analysis procedures from the serum and hypothalamus were described in a previous report [ 12 , 26 ]. Briefly, the serum (0.1 mL) was extracted with 0.3 mL of 3:1 ( v / v ) methanol:chloroform and 0.03 mL of internal standard (IS, 2-chloro-L-phenylalanine, 300 μg/mL).…”
Section: Methodsmentioning
confidence: 99%